ANALISIS KINERJA PELAYANAN RUMAH SAKIT UMUM DAERAH XYZ - Ayuningrum, Niken; Al Rachmat, Ryan; Dini, Maya (JAB (Jurnal Akuntansi & Bisnis), 2019)
This study aims to to analyze the achievement of the performance of the service the district general hospital xyz , as a hospital public service board , the hospital management xyz wanted increase of starting from the quality of facilities and an increase in service facilities and the development of human resources and didn’t forget of an increase in their quality and performance hospital services .In this case the achievement of the performance of the service in terms of two services activity for inpatient or outpatient treatment , to support this secondary data as to the main databank-obtained of a publication at the website of the hospital and to the direct observation of .Based on the performance of the service six indicators of: Bed Occupancy Rate (BOR), Turn OverInterval (TOI), Bed Turn Over (BTO), Average Length of Stay (ALOS), Gross Date Rate (GDR), dan Net Date Rate (NDR). Results showing that the achievement of the performance of the service the hospital suffering an accelerated greenhouse xyz an increase in in the period 2006 to 2013  - 2017.  Keyword : performance, service, hospital, BLU